1999
DOI: 10.1046/j.1463-5224.1999.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of aging and low zinc nutrition on the choroid in the pig: II. The melanosome

Abstract: The effects of low zinc nutrition and aging on central choroidal melanosomes were examined in the pig. Melanosomes of central choroidal melanocytes were morphologically and morphometrically examined in three populations of pigs (young, pregnant and aged), that were maintained on either control (C) or low zinc (LZ) diets. In C groups, the typical melanosomes decreased in size with age, although a subpopulation of larger melanosomes occurred in the oldest group. In contrast, the melanosomes of the animals on LZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
3
9
1
Order By: Relevance
“…We assume that melanosomes without adequate uptake of zinc change their structural and probably functional properties, which was shown before in pig eyes [31][32]. Here we found that this mechanism also applies for rat eyes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We assume that melanosomes without adequate uptake of zinc change their structural and probably functional properties, which was shown before in pig eyes [31][32]. Here we found that this mechanism also applies for rat eyes.…”
Section: Discussionsupporting
confidence: 82%
“…However, while Samuelson et al [32] described them as melanocytes by ultrastructure, we found that they are ED-1 positive macrophages.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Samuelson et al have reported ultrastructural changes in the RPE and choroidal melanocytes of adult pigs when they were maintained on diets deficient in zinc. These included displacement of cone nuclei towards the RPE, swollen outer segments of photoreceptors and altered choroidal melanosomes [31,38,39,82,83]. Cataracts and exophthalmos have been reported in trout and salmon associated with zinc deficiency [64 -67].…”
Section: Cats Dogs Pigs and Fishmentioning
confidence: 99%
“…Although advanced age is associated with increasing prevalence of detrusor underactivity in the clinical setting, 1 we do not believe that this was a significant factor in this study given that the lifespans of these animals are typically >10 years and previous studies involving domestic pigs have considered ages up to 2 years as subadult and >5 years as aged. [27][28][29] Finally, we were unable to accurately assess the role of influential factors including the kinetic features of slow venous drainage and potential autoregulatory changes in compliance and capacitance which may occur in the absence of vascular flow. Thus, the non-zero pressure values witnessed at zero flow reflect an estimate of the bladder vascular filling pressure.…”
Section: Discussionmentioning
confidence: 99%